Street furniture - Uffelen, Chris van. (Salenstein : Braun ; London : Thames & Hudson [distributor], 2010)
Street furniture is the secret star of urban outdoor design. Though rarely noticed at first glance, it significantly contributes towards the urban experience. Benches, fountains, street lamps, rubbish bins, post boxes, tourist information signs, bus stops as well as public toilets are items that reoccur in various urban spaces.
Keywords: Urban landscape architecture; Public spaces -- Design